2004
DOI: 10.1128/jcm.42.2.627-630.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay forHelicobacter pyloriNeeds Adjustment for the Population Investigated

Abstract: Helicobacter pylori infection and peptic ulcer disease are common in developing countries, e.g., Vietnam. An enzyme-linked immunosorbent assay (ELISA) for screening of patients and for seroepidemiology is a useful tool but needs to be validated in the population studied. We used in-house ELISA with sonicated Swedish and Vietnamese strains as antigens to measure immunoglobulin G antibodies after absorption with sonicated Campylobacter jejuni in sera from 270 H. pylori culture-confirmed peptic ulcer patients, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 18 publications
4
55
0
1
Order By: Relevance
“…Nguyen et al reported an increase of H. pylori seroprevalence from 30.9% in children under 3% to 53.1% in 15-18 year group (OR: 1.59; 95% CI: 1.1-2.32) in a study population of 476 children [13]. Our results are comparable with some other findings [13,16,20,21].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Nguyen et al reported an increase of H. pylori seroprevalence from 30.9% in children under 3% to 53.1% in 15-18 year group (OR: 1.59; 95% CI: 1.1-2.32) in a study population of 476 children [13]. Our results are comparable with some other findings [13,16,20,21].…”
Section: Discussionsupporting
confidence: 82%
“…The method had been established and evaluated previously, giving with a cut-off level of OD 0.22 a sensitivity of 93.9% to 99.6% and a specificity of 90.7%. [16]. Since this type of assay can have ±10% variability around the established cut-off level, we used the lower cut-off of 0.2 in order to ensure a high sensitivity in the assay.…”
Section: Variable Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference might be due to several factors: genetic, geographic and socio-economic proper to each population plus to differences in the bacterial strains that originated the antigens used in antibody detection (15). More than 70% of the seropositive subjects used to drink alcohol, sodas and coffee, so this group might have a greater probability to develop gastric pathology.…”
Section: Discussionmentioning
confidence: 99%
“…To test the association between parasites in children and potential polarization of the host immune response to H. pylori, we assayed feces for parasites and serum for IgG responses to H. pylori as noninvasive and sensitive methods to screen for parasitic and H. pylori infections. These assays have been used to estimate prevalence of H. pylori in defined populations (40), and as others have reported (19,22,41), we developed an antigen-specific ELISA for H. pylori because the accuracy of commercial kits for serologic screening for H. pylori infection in children has been questioned (42). Furthermore, commercial kits for measurement of IgG subclass responses to H. pylori are not available.…”
Section: Discussionmentioning
confidence: 99%